A VIDA NA MISSÃO DO METODISMO POÇOS-CALDENSE: uma análise crítica sobre a práxis missionária no âmbito da ação social à luz do Plano para a Vida e Missão - SANTOS, LAYS ROCHA MOREIRA DOS (2018)
The relationship between the evangelistic and social dimensions of missions has always been tensely constituted in the history of the Christian Church. The dichotomic legacy between God-world, spirit-body comes from the greeks, Augustine and is nowadays reinforced by the enlightenment mindset. This inheritance thus sustains and creates possible interpretations such as politics and social work are worldly things; the primal mission of the church is oral preaching; the improvement of social conditions springs from the success of evangelization. However, the history of the Brazilian Methodism finds initiatives in favor of changes in the understanding and practice of missions upon the early '60s; even though it is only in the 80's that such reflexions achieve a wider vision about missions when they become inspired by the reality of the Brazilian society and the Wesleyan inheritance. This process became known as Life and Mission, resulting in the creation of the Plan for Life and Mission of the Church in 1982. Such document remains as a missiological paradigm of the Brazilian Methodist Church, and amongst its content one will find in the "Plan for work and life areas" of the Church the Area of Social Work, which is the interest of this study, since it is recognized as part of the mission and building of the Kingdom of God through acts of love and righteousness in favor of the renovation of the human being and the social structures. The goal is to know and investigate how this relationship works amongst the guidelines brought up with the Plan as they are practiced, which is why the Methodist Church of Poços de Caldas was chosen, due to its involvement with the social and missionary praxis. Bibliographic research was conducted to attain this goal, focusing on the history of Methodism in Brazil with an emphasis on the elements that led to the creation of the Plan. In a second moment, the historical attention is directed to the city of Poços de Caldas, the arrival of Methodism, the social and missionary actions developed by the members of the town, and especially a detailed look towards the activities that are in play to counteract the guidelines presented by the Plan. This is why chapter two brings a mapping of such actions through documental research. The last chapter presents the analysis of the social and missionary praxis of Poços de Caldas' Methodists, but to attain that it was necessary first to define the concept of praxis, which is why the discussion goes through the philosophy and the practical theology that define it as a transforming activity. Nevertheless, there were observations that this political, social, and economic dimension of the praxis is present in the actions of the Methodists, while the conscience is many times centralized in the directors of the Methodist Association of Social Work, specifically because of their direct contact with the practice, daily circumstances, and the contact with those who are hurting. Therefore, upon this diagnosed reality, the research concludes elevating the discussion to the debate of the diaconal ministry of Christ's Church, where every Christian has the responsibility of serving and loving their neighbor